Hubungan Kepatuhan Perawat dalam Penerapan Komunikasi SBAR dengan Ketepatan Identifikasi Pasien di RS X Jakarta Barat - Ade Septiani; Solehudin Solehudin; Sancka Stella (Vitamin : Jurnal ilmu Kesehatan Umum, 2026)
Patient safety is a top priority in healthcare services in hospitals. One of the critical elements is the accuracy of patient identification to prevent incidents such as procedural errors or medication administration. The purpose of this study was to determine the relationship between nurses' compliance in implementing SBAR communication with the accuracy of patient identification at Hospital X, West Jakarta. This study is a quantitative analytical study. The research design used was a cross-sectional study. The population in this study were nurses working at Hospital X, West Jakarta with a sample of 50 respondents taken using the total sampling technique. The data collection technique used an instrument in the form of an observation sheet for SBAR compliance and patient identification accuracy. Data analysis used the Chi-Square statistical test method. Based on the results of the study, it was found that most nurses were not compliant in implementing SBAR communication, namely 27 people (54%) and the majority were not accurate in identifying patients, namely 30 people (60%). The results of the statistical test showed a p value = 0.000 (p <0.05), which means there is a significant relationship between nurses' compliance in implementing SBAR communication with the accuracy of patient identification at Hospital X, West Jakarta. This study indicates that the better nurses' adherence to SBAR communication, the better the accuracy of patient identification. Hospitals are recommended to increase routine supervision and ongoing training to strengthen a culture of patient safety through effective communication.